Innovation, entrepreneurship, and the economy in the US, China, and India : historical perspectives and future trends - Shah, Rajiv, 1953 July-; Gao, Zhijie; Mittal, Harini (London, UK : Academic Press/Elsevier, 2015)
'What drives innovation and entrepreneurship in India, China, and the United States? Our data-rich and evidence-based exploration of relationships among innovation, entrepreneurship, and economic growth yields theoretical models of economic growth in the context of macroeconomic factors. Because we know far too little about the key characteristics of Chinese and Indian entrepreneurs and the ways they innovate, our balanced, systematic comparison of entrepreneurship and innovation results in a new approach to looking at economic growth that can be used to model empirical data from other countries. The importance of innovation and entrepreneurship to any economy has been recognized since the pioneering work of Joseph Schumpeter. Our analysis of the major factors that affect innovation and entrepreneurship in these three parts of the world - US, China and India -provides a comprehensive view of their effects and their likely futures.'--Back cover.
Includes bibliographical references and index.
Keywords: Entrepreneurship -- United States; Entrepreneurship -- China; Entrepreneurship -- India